A decline in sperm quality among men seeking fertility treatment in the State of Pahang: is this a worrying trend? - Abd. Wahab, Azantee Yazmie; Ramli, Roszaman; Zainuddin, Ahmad Murad; Mohd Yatim, Hayati; Md. Ariffin, Norsina (Obstetrical & Gynaecological Society of Malaysia, 2010)
Introduction: Semen analysis is considered the most important indicator of male infertility. Studies demonstrated that semen quality has declined in the past decades. Factors such as age, smoking, occupation and lifestyle could affect semen quality dramatically.